Problematika Pembelajaran Nahwu bagi Tingkat Pemula Menggunakan Arab Pegon - Nailis Sa’adah (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2019)
Nahwu learning, especially in scope of Islamic boarding school is connected well to classical book (Kitab Kuning). It also used translation method of Arab Pegon. Thought nahwu learning is only media, the goal is relative. Nahwu learning should be based on learner ability. This article focuses on the study of learning practices in Islamic boarding school. As the location of the case study the author highlighted the practice in the Ali Maksum’s Islamic boarding school Krapyak Yogyakarta. The approach in this study is qualitative research. This study concluded that Nahwu learning for the beginner level using Arab Pegon metodh was a problem in learning Arabic (Nahwu).